Applications of biomechanics in swimming - Burkett, B. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Swimming is one of the most popular forms of physical activity and competitive sports around the globe. The purpose of this study was to further understand how people move through the medium of water. To address this issue three projects were conducted on elite swimmers (FINA rankings >900) and quantified the biomechanics of swimming via inertial sensors, towing force devices, and bilateral swim ergometers combined with 3D kinematics. The previously unknown parameters of quantifying kick rate and kick have been established; the influence of breathing on the net drag identified; and scientific basis for the Paralympic swimming classification process quantified. Applications of these biomechanical measures add to the pool of knowledge on swimming technique and form the foundation for an evidence-based International Paralympic swimming classification system.